Barriers to increasing the physical activity of people with intellectual disabilities. (30th September 2016) - Cartwright, Luke; Reid, Marie; Hammersley, Richard; Walley, Robert M.
Abstract : Accessible summary: We talked to people with intellectual disabilities and their carers about being healthy. Sometimes it was difficult for people with intellectual disabilities to take part in activities that would help keep them healthy. Being active is not just about doing special sports and activities. It can be part of everyday life. People with intellectual disabilities could become more active and be healthier with help from their carers. Abstract: Background: The prevalence of obesity, inactivity and related morbidity and mortality is higher amongst people with intellectual disabilities than in the population in general, an issue of global concern. This research examined the perspectives of people with intellectual disabilities and their carers, on exercise and activity. Materials and Methods: Qualitative data were collected via interviews and a focus group with people with intellectual disabilities and their paid and family carers, recruited via state‐funded community‐based day centres in Scotland. Results: Three barriers hindered service users with intellectual disabilities from regular involvement in physical activity: (i) acceptance of an inactive lifestyle by carers; (ii) restrictions on activity due to paid carer preferences and resource limitations; (iii) communication issues between family carers and paid carers. Barriers were based on assumptions made by paid and family carers, so there is potential to increase activity by changing attitudes, improving communication and reconceptualising activity as integral to everyday living, rather than as additional exercise requiring special resources. Conclusions: Carers should be supported to promote physical activity in a variety of ways to enhance the motivation of service users, to encourage them to engage with physical activity as an integral part of a healthy lifestyle and to transfer this to their lives beyond day care.